Glass Transition Behavior of Poly Methyl Methacrylate Microplastics Under Various Intermediates Ratio - Kamaruddin, Mohamad Anuar (International Journal of Integrated Engineering, 2019)
In the recent era, a lot of plastic based intermediates have been derived and synthesized. Although the efforts area appealing, there is drawbacks which claimed that this process created another new type of pollution for waste degradation issues. Thus, many methods have been developed to find the best way for plastic waste disposal. Among others, degradation by worm under vermiculture which employs worms as decomposer agent is one of promising method. In this study, the degradation of microplastics namely Poly methyl methacrylate (PMMA) at different ratio of initiator: monomer was synthesized and further tested under vermiculture condition. The mixture was prepared through emulsion polymerization. PMMA was grinded into fine particles and sieved to the size of 500 µm and then mixed with different ratio of cow manure and vermiculture setting was introduced throughout the process. Eudrilus eugeniae was used as decomposer under ambient condition. The rate of PMMA degradation was measured and characterized physically using Differential Scanning Calorimetry (DSC) to identify glass transition temperature (Tg). Thermogravimetric Analysis (TGA) was used to identify thermal degradation of the samples. Four types of PMMA samples were synthesized (PMMA 1, 2, 3 and 4). Laboratory work has demonstrated that the glass transition temperature, Tg of all pure PMMA was found to be in the range of 131°C – 136° C respectively. The optimized sample (PMMA 4) was then further tested under vermiculture at different ratio of cow manure. The result showed that,